Comprehensive Review: Exploring the Impact of Physiotherapy on Post-Traumatic Stress Disorder (PTSD) - ALHUTAYLAH , AMER SALEH ALI; ALQAHTANI, MUBARAK ALI SAEED; ALYAMI, SALEM FARIS MOHAMMED; AL YAMI , IBRAHIM FARIS SAEED; AL MUTARID, ALI MUTARID HAMAD; ALZAMANAN, ABDULMAJEED MAHDI HAMAD; AL YALA, ABDULRAHMAN ABDULLAH SALEH; ALRABAH, ALI ABDULLAH HUSSAIN; AL RABEAH, SALEH ABDULLAH HUSSAIN; AL ZAMANAN, MOHAMMED MANA (Journal of Ecohumanism, 2024)
PTSD is a severe mental health disorder that is found in millions of people across the world and develops from psychological signs that include flashbacks, hyperarousal, and emotional avoidance. However, there is still evidence that PTSD is not limited to the mental health area only and might have a vast effect on physical health, too. In the past, clients with psychosis largely received medication and some form of cognitive/behavioral talk therapy like CBT. It has been in the recent past that literature investigating the part of physiotherapy in PTSD treatment has commenced, whereby they supply therapeutic approaches aimed at handling the mental and physical effects of trauma. Exercise therapy, breathing exercises, and mind-body interventions, including yoga and tai chi, greatly reduce the symptoms of PTSD based on physiotherapy. The purpose of this review is to examine the place of physiotherapy in the treatment of PTSD, discuss the existing literature supporting this profession's application, and explain practical ways physiotherapy may be incorporated into the general, evidence-based PTSD treatment plan.PTSD,